IMPACT OF PLYOMETRIC EXERCISE ON BALANCE REGULATION IN CHILDREN AND YOUTH WITH AUTISM SPECTRUM DISORDER - MANIU, Dragoş Adrian; MANIU, Emese Agnes (Studia Universitatis Babeş-Bolyai Educatio Artis Gymnasticae, 2025)
Background: Motor coordination difficulties and impaired postural stability are commonly observed in children and adolescents with Autism Spectrum Disorder (ASD), often limiting their ability to engage in everyday physical tasks and recreational activities. Although numerous strategies have been implemented to address these motor impairments, the specific impact of plyometric exercise on balance outcomes in this population has not been thoroughly examined. Objective: This research aimed to evaluate the influence of a systematically designed plyometrictraining program on balance control in school-aged individuals with ASD. Methods: Thirty participants (15 control group, 15 experimental group) between the ages of 10 and 15 years, all formally diagnosed with ASD, took part in a 12-week intervention. 15 children participated in plyometric exercise sessions; 15 children did not attend any form of exercise session during the 12 weeks. Pre- and post-training assessments were conducted using two standardized tools: the Mini Balance Evaluation Systems Test (Mini-BESTest) and the balance component of the Bruininks-Oseretsky Test of Motor Proficiency (BOT-2). Results: Statistical analysis demonstrated that the group undergoing plyometric training exhibited significant enhancements in both static and dynamic balance when compared to the control group, with results showing a p-value of less than 0.05. Conclusion: The findings suggest that plyometric training can serve as a beneficial and motivating approach to support balance development in children and adolescents on the autism spectrum.